Investigating the Impact of Environmental Toxicology of Heavy Metals in Fish: A Study of Rivers of Pakistan - Ahmad Manan Mustafa Chatha; Saima Naz; Syeda Saira Iqbal; Unab Zahra (Scientific Inquiry and Review, 2023)
The global concern of heavy metal toxicity has affected all nations, as the discharge of agricultural runoff and untreated industrial waste into water bodies, including rivers, leads to environmental toxicology. This increased level of heavy metals poses risks not only for marine life but also to those who consume them. While fish is an important protein source, consuming contaminated fish containing high levels of heavy metals can have severe adverse effects on human health. Therefore, it is crucial to address these pollution sources effectively in Pakistan, where a significant portion of the population relies on agriculture and fishing for their living. The country's rapid industrialization and urbanization have substantially increased pollutants in its rivers and other water bodies. The current body of research has indicated that the elevated levels of heavy metals in the ecosystem, including the Indus River, pose a significant threat to the local ecosystem and the well-being of marine life. Heavy metal pollution in Pakistani rivers originates from multiple sources, such as industrial effluents, agricultural runoff, and municipal waste. The unregulated discharge of industrial waste into rivers is a major contributor to heavy metal pollution in Pakistani rivers. Moreover, the excessive and uncontrolled use of fertilizers and pesticides in agriculture equally contributes to the contamination of rivers with heavy metals. The current study is a review article, which provides a comprehensive explanation of how environmental toxicology affects the ecosystem, especially concerning the rivers of Pakistan.